The harmony of the works of Dospambet Zhyrau and the Boatman Kul Mustafa - Zhalelov Д.С.; Arslan М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The connection between the Turks of Anatolia and the Kazakhs runs deep, with their literature, culture, language, and mentality emanating from a shared source. This article delves into the internal harmony of contents, historical and literary parallels in the works of Dospambet Zhyrau and the Boatman Kul Mustafa. Dospambet Zhyrau, an artist with a syncretic approach, delves into the origins and roots of folk poetry. Born in the city of Azau in the 16th century, as described in his memoirs, the main theme of his works (tolgau) that has come down to us revolves around struggle, liberation, freedom, longing, and the search for meaning in the life of an ideal person who harbors no regrets. The Boatman Kul Mustafa stands out in the literature of the Turkish people, notably in maritime literature. Living in the 17th century during the Ottoman Empire, Kul Mustafa, a reliable companion of Murat Reis in sea voyages, participated in the military tour to conquer Baghdad. Limited information about his biography has survived, but some of his works, including the renowned saga "Young Osman," endure. The bravery of Osman, the young hero, became widely known among the Turkish people through Mustafa the Boatman’s saga. The article not only defines the internal content harmony and methods of comparison and analysis in the stories of Boatman Kul Mustafa and Dospambet Zhyrau but also describes the syncretism of these two personalities, significant in the folk poetry of related peoples. Conclusions drawn from the perspectives of Kazakh and Turkish researchers add depth to the exploration. Understanding the harmony of thought between these two creative personalities holds relevance and importance for modern science, shedding light on broader cultural and historical implications.